Tracker Sistem Pipa Tarik Pembuka Bearing Beralur (Snap Bearing) - Yusri Yusri; Nasirwan Nasirwan; Zulfikar Zulfikar (Jurnal Teknik Mesin, 2004)
In the transmission box of the car used snap bearing that hold by a snap ring, There was a difficulty to remove this bearing from body of the box because the bearing just stick the head out about 2.5 mm include the lib of snap groove. The process to take out bearing more difficult if bearing have used for along time, because bearing was sticky hard to the body and axis. Occasionally the tool to take out bearing from the body use tracker with two plate system. The plate clamp bearing at two side and pull out by two bolt at each plate, and the pulling often unbalance and that cause bearing at an angle and it make the-process more difficult. Some time cause bearing is broken end tip or point of bolt destroyer the body of transmission box because tip of bolt rest on body. So that we troy to make a trekker with split pipe pulling. Pulling doing by the hook at inside of split pipe. 5o the split pipe can hook all round of the bearing groove. Split pipe joint by a pipe nut with pulling bolt inside. The bolt will rest on center of axis, so the bearing can take out balance because the pulling done exactly at the center of bearing, and bearing come out easily and it is not damage the body of transmission box.